Lived Experiences of Cyber-bullying Victims in a Higher Educational Institution in Las Piñas City - Zamuco, Maria Jonathan C.; Villa, Elizabeth B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Technology has modernized our lives, but it has also led to the rise of cyber-bullying, a global issue that can lead to psychological distress, traumatic experiences, poor mental health, suicidal thoughts, and even self-harm. Research shows that college students often experience increased stress, depression, anger, and irritability due to cyber-bullying. Laws criminalizing cyber-bullying offenses include cyberstalking, cybersex, identity theft, and online libel. At the University of Perpetual Help System DALTA-Las Piñas Campus, ninety students have reported experiencing cyber-bullying. This study aims to provide valuable information for tailoring cyber-safety prevention programs for college students and to raise awareness about the issue. The findings will help universities develop strategies to minimize or completely eradicate cyber-bullying, and the research will be pioneering in this institution. Thus, the study of cyber-bullying at the University of Perpetual Help System DALTA Las Piñas Campus provides a profound understanding of the multifaceted impact of cyber-bullying on students. The findings reveal the deep emotional, psychological, and social scars left by cyber-bullying, as well as the coping mechanisms employed by victims to navigate their lived experiences. Lastly, the study recommended the need for comprehensive intervention strategies and supportive policies within educational institutions. By fostering resilience and creating a safer environment for students, schools can help mitigate the devastating effects of cyber-bullying and promote a culture of respect and empathy.